Tribes In The Prakāmakāmarūpam: A Cultural Panorama - Kalita, Rijumani (International Journal of Psychosocial Rehabilitation, 2020)
March, 1911 in a poor Brāhmin family. His father was late Shyamadeva Sarma and mother was late Bhogesvari Devi. Ācārya Manoranjan Shastri has various contributions to Sanskrit literature as well as other branches of learning. He composed a good number of scholarly works in the world of Sanskrit as well as Assamese learning. He composed three Sanskrit works, viz. the Patākāmnāya, the Utaṅkabhaikṣam and the Prakāmakāmarūpam. Assam, a northeastern state of India known for its rich cultural diversity, is home to several indigenous tribes, each with its unique traditions, languages, and customs. A tribe is a group of distinct people, dependent on their land for their livelihood, who are largely self-sufficient and not integrated into the national society. In the Prakāmakāmarūpam, it has found the description about several tribes who lived in different places of Assam. There are mainly two tribes found in Assam-Hill tribes and Plain tribes. Manoranjan Shastri has given the names of hill tribes who lived in the North-East frontier part of Assam from Paraśurāmakuṇḍa to Manipur which he indicates as Bhārgavakṣetra. He gives the list of hill tribes as follows- Abara, Micimi, Daphala, Aka, Nakte, Galan, Phombari, Khova, Banco, Moklum, Miji etc. Again, he indicates the name of Cimpho, Khamti, Monpa, Bhota, Miri, Devari etc. Another some hill tribes also lived in the different parts of Assam, such as- Khasi, Naga, Garo, Kuki, Miju, Mikir, Jayanta etc. are given in the book with special reference to their life, nature and culture.